The divine sublime: Educating spiritual teachers in Emerson’s divinity school address - Blackmer, Corinne E. (Approaches to Teaching the Works of Ralph Waldo Emerson, 2018)
A leader of the transcendentalist movement and one of the country's first public intellectuals, Ralph Waldo Emerson has been a long-standing presence in American literature courses. Today he is remembered for his essays, but in the nineteenth century he was also known as a poet and orator who engaged with issues such as religion, nature, education, and abolition.This volume presents strategies for placing Emerson in the context of his time, for illuminating his rhetorical techniques, and for tracing his influence into the present day and around the world. Part 1, "Materials," offers guidance for selecting classroom editions and information on Emerson's life, contexts, and reception. Part 2, "Approaches," provides suggestions for teaching Emerson's works in a variety of courses, not only literature but also creative writing, religion, digital humanities, media studies, and environmental studies. The essays in this section address Emerson's most frequently anthologized works, such as Nature and "Self-Reliance," along with other texts including sermons, lectures, journals, and poems.
Keywords: Language Arts & Disciplines / Study & Teaching; Literary Criticism / American / General; Literary Criticism / Modern / 19th Century; dept.eng